Measured daylighting potential of a static optical louver system under real sun and sky conditions. (October 2015) - Konis, Kyle; Lee, Eleanor S.
Abstract: By utilizing highly specular surfaces and engineered profile geometry, optical sunlight redirecting systems integrated into the overhead "clerestory" zone of the building facade present the potential to enlarge the daylighting zone by redirecting the luminous flux incident on the window deeper into the space than conventional shading systems. In addition, by developing system geometry to redirect daylight to specific zones within the space, optical light redirecting systems have the potential to avoid the glare conditions commonly produced by conventional facade shading systems that direct significant amounts of daylight below head height into the occupant's field of view. In this case study, side-by-side comparisons were made over solstice-to-solstice changes in sun and sky conditions between an optical louver system (OLS) and a conventional Venetian blind set at a horizontal slat angle and located inboard of a south-facing, small-area, clerestory window in a full-scale office testbed. Daylight autonomy (DA), window luminance, and ceiling luminance uniformity were used to assess performance. The performance of both systems was found to have significant seasonal variation, where performance under clear sky conditions improved as maximum solar altitude angles transitioned from solstice to equinox. Although the OLS produced fewer hours per day of DA on average than the Venetian blind, the OLS never exceeded the designated 2000 cd/m 2 threshold for window glare. In contrast, the Venetian blind was found to exceed the visual discomfort threshold over a large fraction of the day during equinox conditions (from 40 to 64% of the test day between August 22 and October 12). Notably, these peak periods of visual discomfort occurred during the best periods of daylighting performance. Luminance uniformity was analyzed using calibrated high dynamic range luminance images. Under clear sky conditions, the OLS was found to increase the luminance of the ceiling as well as produce a more uniform distribution of luminance over the ceiling. Compared to conventional venetian blinds, the static optical sunlight redirecting system studied has the potential to significantly reduce the annual electrical lighting energy demand of a daylit space and improve the quality from the perspective of building occupants by consistently transmitting useful daylight while eliminating window glare. Highlights: An optical louver system was compared against a Venetian blind in a test facility. Comparisons were made over seasonal changes in sun and sky conditions. Performance assessed with Daylight autonomy, luminance, and luminance uniformity. Optical louver systems can achieve effective daylighting while eliminating glare.